Potentiometric and conductometric studies on the system acid-isopolytungstate and the formation of lanthanum tungstates - Prasad, Saradh; de Santana, Renato Alexandre Costa; Campos, Ana Regina Nascimento; Leite, Valderi Duarte (Eclética Química, 2007)
The stoichiometry of the polyanions formed by the action of nitric acid on sodium tungstate (≤ 0.01M) has been studied by means of electrometric techniques involving pH-potentiometric and conductometric titrations. The well defined inflections and breaks in the titration curves provide evidence for the existence of the polyanions, para-W 12 O 4110- and meta-W 12 O 396- corresponding to the ratio of H + :WO 42- as 7:6 and 9:6 in the pH ranges 5.7-6.0 and 3.6-4.1, respectively. The interaction of lanthanum nitrate with sodium tungstate solutions, at specific pH levels 8.0, 5.9 and 4.0 was also studied by pH and conductometric titrations, in aqueous and alcoholic media, with each of the reagents alternatively used as titrant. The electrometric experiments provide definite evidence of the formation of normal-La 2 O 3 .3WO 3 , para-5La 2 O 3 .36WO 3 and meta-La 2 O 3 .12WO 3 tungstates in the vicinity of pH 6.3, 5.0 and 4.2, respectively. Analytical investigations on the precipitates formed confirm the results of the electrometric study.